Characterization of deep ore-forming fluid in the Zhaoxian gold deposit within the Jiaodong gold province: insights from quartz vein fluid inclusion, in-situ trace element analysis, and S isotopic composition in pyrite - Zhang, Zheming; Zeng, Qingdong; Fan, Hong-Rui; Bai, Rui; Wu, Jinjian; Li, Xinghui; Zhang, Yongwen; Huang, Liangliang (Frontiers in Earth Science, 2024)
The Jiaodong gold province, situated in the southeastern margin of the North China Craton, is globally renowned for its substantial gold reserves exceeding 5,000 tonnes. The Zhaoxian gold deposit is part of the significant Jiaojia gold belt within the Jiaodong gold province. Fieldwork has identified four distinct stages of ore formation in this study: an early barren quartz vein stage (Stage 1) containing fine-grained pyrite; a gold-bearing stage (Stage 2) consisting of quartz, pyrite, and native gold; a polymetallic sulfide-rich stage (Stage 3) comprising quartz, polymetallic sulfides, and native gold; and a late-stage (Stage 4) primarily composed of quartz and calcite with minimal pyrite content. We conducted fluid inclusion analysis using microthermometry and Raman spectroscopy techniques to examine the fluid characteristics. In-situ analysis of trace elements in pyrite was performed to investigate the fluid composition and evolution. Additionally, we determined the sulfur isotope composition in pyrite to analyze the source of sulfur. Our findings indicate that the ore-forming fluid in the Zhaoxian gold deposit belongs to a medium-to-low-salinity H₂O-NaCl-CO₂-CH₄ system. Fluctuations in Au and As concentrations observed along with oscillating zones and sulfide inclusions during Stage 2 suggest potential fluid boiling processes occurring during mineralization. High concentrations of Ag, Cu, Zn, Cd, In, Pb, and Bi without oscillating zones during Stage 3 imply precipitation of polymetallic sulfides under stable fluid conditions. The δ34S values observed in the Zhaoxian gold deposit are slightly higher than those found in granitoids from other areas within Jiaodong but similar to those seen in other deposits within the Jiaojia gold belt region. In conclusion, magmatic-hydrothermal ore-forming fluids were involved along with significant fluid-rock interaction during metallogenic processes of the Zhaoxian gold deposit.